Development of u-shaped two-phase hollow fiber-liquid-phase microextraction for food mycotoxins analysis by using liquid chromatography tandem mass spectrometry / Ali Mohamed Ali Alsharif - Ali Mohamed , Ali Alsharif (2019)
This study is focusing on the development and validation of an analytical method for the determination of Aflatoxins (AFB1, AFB2, AFG1, and AFG2) and Ochratoxin A (OTA) in food samples. The first part is the LC-ESI-QQQ-MS/MS optimization using response surface methodology combined to Quick, Easy, Cheap, Effective, Rugged, and Safe method (QuEChERS) for the determination of mycotoxins in the different food matrix. The mobile phase composition is optimized using univariate methodology. While the experimental methods were optimized using multivariate strategy, i.e. Plackett- Burman and Box Behnken designs (BBD). The optimized LCMS parameters were subjected to method validation, which revealed good repeatability (0.63-4.76%), IDL (1.41 -3.61 ng), and R2 (0.9992-0.9999) in standard and spiked samples. The validated LC-MS/MS combined with QuEChERS method was successfully applied for the determination of Aflatoxins and Ochratoxins A in a variety of food matrices. The results demonstrated good sensitivity with LOD ranged from 0.05-0.10 μg/Kg, and LOQ ranged from 0.08-0.30 μg/Kg. The results have revealed a good intra-day and inter-day precision below the acceptance limit of the method (˂20%) with recovery ranged between 81.94- 101.67%.In the second part of the study, U-Shape hollow fiber liquid phase microextraction (U-Shape-HF-LPME) supported by extraction/dispersion solvent was developed for the analysis of Ochratoxin A (OTA) in a food sample using both univariate and multivariate optimization (central composite design (CCD)) strategy. In the last part of the study, the U-Shape hollow fiber liquid phase microextraction (U-Shape-HFLPME) supported by extraction/dispersion solvent also was developed for the analysis of Aflatoxins (AFB1, AFB2, AFG1, and AFG2) in a food sample using both univariate in fruit juice. Moreover, QuEChERS and UAE were optimized and combined with HFLPME for nonliquid food samples. The developed methods were successfully applied for the analysis of OTA as well as Aflatoxins (AFB1, AFB2, AFG1, and AFG2) in liquid and non-liquid food samples, in which three food samples were shown to contained trace amount of OTA and five food samples also shown to contained trace amount of aflatoxins below the maximum level allowed in the European Legal Maximum Limit. The results revealed satisfactory performance in the term of linearity, LOD, LOQ, precision, and accuracy and fulfilled the method performance criteria of Commission Regulation (EC) No 401/2006 and Sanco, 2013. The correlation coefficient (R2) is higher than 0.9906. The limit of detection was in the range of 0.04-0.09 μg/L, while the quantification limit ranged from 0.8- 0.2 μg/L. The method showed good precision (<14% RSD) with recovery from 75.38-107.39%.